Upaya Pemberian Dukungan Sosial terhadap Penyesuaian Diri Remaja di Panti Asuhan Kasih Setia Medan - Sherina Maria Sihombing; Berlianti (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
English translation. Adolescence is the transitional phase from children to adults. It is in adolescence that children feel emotional instability that makes adolescents easily stressed when facing problems. Moreover, the teenager is also easily affected by the outside world he sees without filtering out whether it is good for his development or not. Therefore, adolescents need social support from their surroundings. The social support obtained from the surrounding environment helps adolescents in their emotional development, so that adolescents are not easily stressed about the problems they face and are confident in solving them. This article is intended to strive for the provision of social support carried out by the author which is useful for the self-adjustment of the children of the Kasih Setia Orphanage Medan. The method carried out is the casework stage method proposed by Zastrow including the Engagement, Intake and Contract Stages, Assessment Stages, Intervention Stages, Planning Stages, Evaluation Stages and Termination Stages. With the social support provided by the author in the form of activities and programs, it is hoped that it can help increase the confidence and openness of orphanage children to the surrounding environment.